Timely Recognition of Abusive Injuries (TRAIN): Results from a Statewide Quality Improvement Collaborative. Issue 2 (10th March 2023) - Crichton, Kristin Garton; Spencer, Sandra; Shapiro, Robert; McPherson, Paul; Izsak, Eugene; McDavid, Lolita M.; Baker, Carrie; Thackeray, Jonathan D.; ,
Abstract : Introduction: Early recognition of physical abuse is critical as children often experience recurrent abuse if their environment remains unchanged. The Timely Recognition of Abusive Injuries (TRAIN) Collaborative was a quality improvement network of 6 Ohio children's hospitals created in 2015 to improve the management of injuries concerning for abuse in infants. TRAIN's first phase sought to reduce recurrent abuse by recognizing and responding to injured infants. This study aimed to reduce reinjury rate among infants ≤6 months by 10% at 1 year and 50% by 2 years and sustain improvement for 1 year as reflected in 3- and 12-month reinjury rates. Methods: The TRAIN Collaborative adopted the Institute for Healthcare Improvement's Breakthrough Series Collaborative Model, where partnerships between organizations facilitate learning from each other and experts. Collaborative members identified opportunities to improve injury recognition, implemented changes, responded to data, and reconvened to share successes and obstacles. As a result, institutions implemented different interventions, including education for clinical staff, increased social work involvement, and scripting for providers. Results: Data collected over 3 years were compared to a 12-month baseline. The number of injuries increased from 51 children with concerning injuries identified monthly to 76 children sustained throughout the collaborative. However, within 2 years, the 3- and 12-month reinjury rates ultimately significantly decreased from 5.7% to 2.1% and 6.5% to 3.7%, respectively. Conclusion: Our data suggest the Institute for Healthcare Improvement's Breakthrough Series model can be applied across large populations to improve secondary injury prevention in infants.